From Patrilineal to Bilateral: A New Balance of Islamic Inheritance Law in Indonesia’s Religious Court - Jalaludin, Akhmad (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2024)
This study investigates the transformation of the Islamic inheritance system within the framework of the Religious Courts in Indonesia. Employing a normative legal research methodology, the study adopts conceptual, philosophical, and prescriptive approaches to analyze key legal materials, including the Compilation of Islamic Law (KHI), Supreme Court jurisprudence, and other legal sources. The finding reveals that this transformation is driven by the necessity to align inheritance laws with Indonesia’s inclusive and egalitarian social and cultural values. The implementation of the KHI and the rulings of the Supreme Court represent a significant step toward adopting a bilateral inheritance system aimed at ensuring a more equitable distribution of inheritance rights, particularly for women. Judges’ reliance on the principle of maṣlaḥah (public interest) is crucial in facilitating this transformation. Despite these advancements, challenges persist, especially in increasing public awareness and acceptance of the reformed system. This progressive reform highlights Indonesia’s Religious Court efforts to make Islamic law more responsive to the principles of gender equality. The article offers valuable insights into the evolution of Islamic inheritance law in Indonesia, contributing to broader discussions on promoting gender justice within the framework of Islamic legal principles.